Effect of community intervention on the level of Dengue fever/dengue hemorrhagic fever knowledge and practices in two rural communities in Vietnam - Tham, Chi Dung.
The effect of community-based intervention on the level of dengue fever/dengue hemorrhagic fever (DF/DHF) knowledge and practice was evaluated in two rural communities (Di Su and Xuan Tien), which were purposively selected in North Vietnam. The data were part of a cross-sectional study conducted in 1999 following the implementation of a community-based intervention project in the country. A total of 512 household heads were selected using a simple random systematic sampling method. The findings showed that the magnitude of the POR between intervention package and knowledge of (1) the disease, (2) vector characteristics and (3) preventive measures after adjusting for the confounding effects of age and sex using the multivariate logistic regression analysis were 5.67 (95%CI: 2.16-14.89), 3.87 (95%CI: 2.29-6.52) and 52.54 (95%CI:30.87-89.42), respectively. The relationship between intervention package and overall practice adjusted for confounding effects of age, sex, knowledge of vector characteristics and of prevention measures was 3.22 (95%CI: 1.65-6.31). Furthermore, the study also provided significant evidences of the important role of knowledge in changing the behaviors for the prevention of dengue transmission. The adjusted POR of the relationship between knowledge of (1) the disease, (2) vector characteristics and overall practice was 3.15 (95%CI: 1.09-9.06) and 2.59 (95%CI: 1.38-4.86), respectively after adjusting for age, sex and the other categories of knowledge. Furthermore, the strongest relationship was between knowledge of preventive measures and overall practice (OR = 9.84; 95%CI: 4.84-19.98). In conclusion, the community-based intervention increased the knowledge related to DF/DHF and improved the overall practice on preventive measures. Furthermore, the increase of knowledge, especially knowledge of preventive measures influenced positive change in behavior against dengue transmission.
Vita.
Thesis (MS Epidemiology, Public Health) -- University of the Philippines, Manila
Keywords: Dengue; Community health services